PENGARUH PENGGUNAAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR KETERAMPILAN MENULIS KARANGAN NARASI PADA MURID KELAS IV SD NEGERI BONTOMAERO II KECAMATAN BAJENG KABUPATEN GOWA - Rajab, Hikma; Akhir, Muhammad; Akbar, Amal (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
ABSTRACTThis study aims to determine the effect of using the Explicit Instruction model on the learning outcomes of narrative writing skills in grade IV students of SD Negeri Bontomaero II, Bajeng District, Gowa Regency. This type of research is a pre-experimental design and the research design used is one group pretest-posttest design, which is a study carried out with measurements before the pretest and after the posttest. The sample in this study was grade IV with a total of 17 students, 7 male students and 10 female students. The data collection techniques used were the initial test (pretest), treatment (treatment), and final test (posttest). The results of this study indicate that the average score before being given treatment was 52.35% and after being given treatment it became 77.94% with the results of the hypothesis test showing a tcount ˃ ttable value of 9.022 ˃ 2.12. Thus, the hypothesis proposed in the study reads